The Wardah Effect: Mengapa Produk Ini Menjadi Pilihan Utama - Faisa Maylani Saputri; Lutfia Nur Aini; Trianing Arofah; Ruth Natalia Susanti (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The purpose of this study is to assess the impact of halal brands, brand image, and price perceptions on the motivation and purchasing choices of Wardah consumers, as well as to identify the psychological and behavioral factors underlying the phenomenon of "The Wardah Effect" among Indonesian people. This study uses a descriptive quantitative approach supported by qualitative data. A total of 21 Wardah respondents aged 18 to 27 years old in Kudus were selected as respondents through purposive sampling techniques. Data was collected online using a questionnaire with a Likert scale and open-ended questions. The results showed that three main factors greatly influenced "The Wardah Effect", namely value (halal image and pride in local products), economic efficiency (affordable prices), and ease of access (easy to find). Most respondents felt proud of local products (81.0%), found the prices offered affordable (95.2% agreed), and thought that the products were easy to find (90.5%). Halal imagery is also the most influential component, which provides a sense of security and trust (76.2% fully agree). Promotions and advertisements had an impact on 80.9% of respondents. It was concluded that Wardah's purchase decision was based on three types of rationality, namely economic, cultural, and ideological, as well as social-digital, thus making Wardah a symbol of identity and social values for the younger generation.